2011
DOI: 10.1002/jctb.2722
|View full text |Cite
|
Sign up to set email alerts
|

Influence of moisture content on the specific methanogenic activity of dry mesophilic municipal solid waste digestate

Abstract: The objective of this study was to evaluate the influence of moisture content on the specific methanogenic activity (SMA) of a fresh dry mesophilic digestate from a municipal solid waste digester plant. For this purpose, SMA tests were performed under mesophilic conditions in 500 mL glass bottles of volume used as batch reactors, during a period of 20-25 days. Cellulose, propionate and acetate were used as substrates (5 g COD kg −1 digestate) at four different moisture contents, ranging from 65 to 82%. The moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 10 publications
6
22
0
3
Order By: Relevance
“…Figure 2 reports the final specific methane yield, measured at the end of each experiment, as a function of the TS content and subtracted of the respective blank production. Such a result is consistent with previous findings (Abbassi-Guendouz et al, 2012;Fernández et al, 2008;Le Hyaric et al, 2012;Li et al, 2011;Liotta et al, 2014) obtained using different biodegradable substrates (Table 4), and confirms that the conversion of acids to methane by methanogenic bacteria can be negatively influenced by the lack of water (Lay et al, 1997a;Lay et al, 1997b). Table 3 reports the cumulative methane production of the substrate, the inoculum (blank) and their mixture, as well as the final methane yield of the substrate (Figure 2) and the mixture (Figure 1), showing a lower TS content favours the final methane yield.…”
Section: Bio-methane Productionsupporting
confidence: 94%
See 1 more Smart Citation
“…Figure 2 reports the final specific methane yield, measured at the end of each experiment, as a function of the TS content and subtracted of the respective blank production. Such a result is consistent with previous findings (Abbassi-Guendouz et al, 2012;Fernández et al, 2008;Le Hyaric et al, 2012;Li et al, 2011;Liotta et al, 2014) obtained using different biodegradable substrates (Table 4), and confirms that the conversion of acids to methane by methanogenic bacteria can be negatively influenced by the lack of water (Lay et al, 1997a;Lay et al, 1997b). Table 3 reports the cumulative methane production of the substrate, the inoculum (blank) and their mixture, as well as the final methane yield of the substrate (Figure 2) and the mixture (Figure 1), showing a lower TS content favours the final methane yield.…”
Section: Bio-methane Productionsupporting
confidence: 94%
“…It is worth noting a decreasing trend of the initial methane production rate when increasing the TS percentage as already observed during the AD of other organic wastes more or less rapidly biodegradable: dehydrated sludge mixed with dry kitchen waste (Lay et al, 1997a), waste excavated from a sanitary landfill (Mora-Naranjo et al, 2004), paper waste (Pommier et al, 2007), cellulose (Le Hyaric et al, 2012) and cardboard (Abbassi-Guendouz et al, 2012). At a lower TS concentration, owing to the increasing water content and to the more favourable transport and mass transfer conditions, it seems plausible that the microorganisms are better sustained with soluble substrates (Mora-Naranjo et al, 2004), so that the process takes place more rapidly.…”
Section: Bio-methane Productionmentioning
confidence: 66%
“…Research by Fernandez et al (2008) showed that the methane yield at 30% solids content was 17% less than that at 20%. Le Hyaric et al (2012) observed that TS content affects the various steps of the AD process: hydrolysis, acidogenesis, acetogenesis and methanogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to it generating less water waste, having lower energy demands for heating and with a low‐moisture digestate, SS‐AD is more suitable for lignocellulosic biomass, such as agricultural byproducts, farm waste and energy crops . However, compared to L‐AD, inadequate mass transfer and high organic loading in SS‐AD result in reduced methane yields and a greater tendency to accumulate inhibitors, such as volatile fatty acids (VFAs) and ammonia . In order to avoid these disadvantages, leach‐bed reactors (LBRs) using leachate recirculation help increase moisture content, improve mass transfer and dilute inhibitory compounds, thereby providing significant potential among solid‐state processes .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] However, compared to L-AD, inadequate mass transfer and high organic loading in SS-AD result in reduced methane yields and a greater tendency to accumulate inhibitors, such as volatile fatty acids (VFAs) and ammonia. [14][15][16] In order to avoid these disadvantages, leach-bed reactors (LBRs) using leachate recirculation help increase moisture content, improve mass transfer and dilute inhibitory compounds, thereby providing significant potential among solid-state processes. 17,18 Under these conditions, leachate recirculation management, an important role in this process, has been examined.…”
Section: Introductionmentioning
confidence: 99%